Isolation and identification of bacteria in different street vended foods collected from selected areas of Bangladesh - Paul, Torun Kumar; Roy, Snigdha Rani; Sarkar, Pankaz Roy; Tarafder, Moniruzzaman; Saha, Tapu Kumar (Asian-Australasian Journal of Food Safety and Security, 2018)
Street food vending has become an important public health issue and a great concern to everybody. This is due to widespread food borne diseases, due to the mushrooming of wayside food vendors who lack an adequate understanding of the basic food safety issues. Major sources contributing to microbial contamination are the place of preparation, utensils for cooking and serving, raw materials, time and temperature abuse of cooked foods and the personal hygiene of vendors. The objective of the study was to explore the microbiological quality of different street food; Chotpoti, Chanachur, Amra (Spondias mombin) and Jolpai (Elaeocarpus serratus (Veralu / Ceylon Olive) sold by various street vendor at Khulna city, Bangladesh. A total of 20 samples were collected randomly from street vendors and tested for the presence of bacteria following standard microbiological method used for isolation, enumaration and identification of bacreria. All the examined samples were contaminated by various types of bacteria. The total viable count (TVC) in different street food samples was ranged from 9.6 x 10 CFU/g to 5.9x10 CFU/g. Among samples Escherichia coli 8(40%), Staphylococcus spp. 5(25%), Klebsiella spp. 4(20%), Salmonella spp. 1(5%) and Shigella spp. 2 (10%) were isolated. Escherichia coli were found highest 3(50%) Jolpai samples, then another organisms Staphylococcus spp. was found highest 2(50%) in Chotpoti and then Klebsiella spp. was found one in each sample. Therefore, application of sound risk analysis policies is being advocated to provide a scientific base to the host of risk management option which Bangladesh may need to explore to ensure public health and safety. Asian Australas. J. Food Saf. Secur. 2018, 2(2), 65-70